Pengaruh Kesadaran Wajib Pajak, Kualitas Pelayanan Fiskus, dan Penerapan E-Filing terhadap Kepatuhan Wajib Pajak Orang Pribadi di KPP Pratama Jayapura - Dwi Lestari; Syaikhul Falah; Ulfah Rizky Muslimin (Juara: Jurnal Riset Akuntansi, 2023)
This study aims to examine what are the factors that influence taxpayer compliance using the variables of taxpayer awareness, tax authorities service quality, and e-filing implementation. Collecting data in this study using a questionnaire. The regression model used in this study is a multiple linear regression model with the help of the SPSS program. The research sample was selected using a purposive sampling method of 100 taxpayers. The results of the study show that taxpayer awareness has an effect on taxpayer compliance, while the quality of tax administration services and the implementation of e-filing have no effect on taxpayer compliance, and have an effect simultaneously.